Understanding the misophonic experience: a mixed method study - Ozuer, Yesim; Cima, Rilana; Kestens, Elke; Van Diest, Ilse (Frontiers in Psychology, 2025)
Misophonia is a poorly understood condition in which intense distress is experienced in response to mostly orofacial stimuli. To better understand why specifically anger and disgust seem to characterize this distress, we investigated meanings conveyed by misophonic trigger stimuli in two studies. Study 1 explored these meanings and emotions in two small focus groups (n = 3, n = 5) of misophonia sufferers. Four meaning—themes were generated based using reflexive thematic analysis: “intrusion,” “violation,” “offense,” and “lack of autonomy.” Also, four emotional reaction themes were constructed: “anger/defensive rage,” “disgust,” “fear,” and “safety behaviors.” Study 2 aimed to corroborate the findings of Study 1 in a large, independent sample. To this end, misophonia symptom severity was assessed in 431 young adults using the Amsterdam Misophonia Scale (A-Miso-S). Participants rated the extent to which the meanings and reactions identified in Study 1 matched their experiences with prototypical misophonic trigger stimuli. The meanings showed a positive, moderate correlation with misophonia symptom severity and accounted for 35.15% of the variance in A-Miso-S scores. An exploratory factor analysis identified two factors explaining 50% of the variance in the meanings and reactions. Factor 1, “Avoidance of intrusive/disgusting stimuli” had high and unique loadings on avoidance, intrusion, and disgust. Factor 2, “Autonomy/Violation,” had high and unique loadings on violation, lack of autonomy, offense, and defensive rage. These findings suggest that the meanings of intrusion, violation, and lack of autonomy are inherent to the misophonic experience, with potential implications for treatment strategies.